Pengesahan instrumen kematangan emosi pelajar bermasalah disiplin: Satu analisis penerokaan faktor (EFA) [Instrument validation of emotional maturity among disciplinary students: Exploratory factor analysis (EFA)] - Mohd Sani, Ismail; Noradilah, Abdul Wahab; Najmi, Muhamad (2019)
This study aims to review the emotional maturity instruments of discipline students at school. A total of 100 students were involved as respondents in this study. This scale measures a list of five broad factors of Emotional Immaturity: Emotional Unstability, Emotional regression, social maladjustment, personality disintegration and lack of independence. Emotional Maturity Scale was developed by Singh and Bhargava. The data were analyzed descriptively by using Alpha Cronbach reliability and EFA analysis using SPSS software. The results of the analysis showed that Alpha Cronbach value obtained was good ie exceeding 0.60. Results from the exploration factor analysis show five factors with Eigen values greater than 1.0. The KMO value (Kaiser-MeyerOlkin) 0.667> 0.6 indicates the items in sufficient emotional maturity variables for intercorrelation. While the Bartlett Test was significant (Chi Square 135.695, p <0.05), the value of the anti-image value (Measure of Sampling Adequancy, MSA) for item correlation exceeds 0.6. However, there are some items that need to be removed because the value obtained is less than 0.60 B2, B8, B9, B12, B14, B21, B28, B29, B30 and B43. The total value variance explained by these five factors is 66,196. The overall findings show that items for emotional maturity instruments can measure and answer research objective.